Pembuatan Pupuk Organik Dari Limbah Tandan Kosong Kelapa Sawit Dengan Penambahan Aktivator Effective Microorganisms - ( Em4 ) Dan Mikro Organisme Lokal Bonggol Pisang Sebagai Peningkat Nutrien Produk - Imanuddin, Teuku (Jurnal Riset, Inovasi, Teknologi & Terapan, 2024)
Empty oil palm fruit bunches have been utilized as raw material for organic fertilizer. This research aims to determine magnesium levels, nitrogen levels, phosphorus levels, potassium levels in organic fertilizer from empty oil palm fruit bunch waste with the addition of effective microorganisms - 4 (EM4) activator and local banana hump microorganisms as product nutrient enhancers and compared with N levels. , P, K contained in the Minister of Agriculture Regulation Number 70/Permentan/SR. 10/140/2011. Tests were tested using the Kjedahl method, UV-VIS Spectrophotometer, Atomic Absorption Spectrophotometer (AAS). The results of this study showed that the highest magnesium levels in samples (30 ml EM4 60 ml MOL) and (30 ml EM4 90 ml MOL) were 0.58%, the highest phosphorus levels in samples (90 ml EM4 150 ml MOL) and (150 ml EM4 90 ml MOL) which is 0.25%, The highest nitrogen content of some of the best samples is shown in the sample (90 ml EM4 150 ml MOL) with a result of 37%, The highest potassium content of some of the best samples is shown in the sample (150 EM4 150 MOL ) with a yield of 1.14%. The levels of N, P, K in this organic fertilizer do not meet the quality requirements for organic fertilizer with a minimum of 2%, but the high concentration of effective microorganisms - 4 (EM4) has a big influence on the decomposer of empty oil palm fruit bunches and local microorganisms of banana hump can increase organic fertilizer nutrients. .